Performance of Profit and Non-profit Rural on School Performance in Qom Province in 2020 - Hamidreza Sheikholeslam; Hossein Khanifar; Abolfazl Bakhtiari (Zanjan University of Medical Sciences and Health Services, 2021)
Background: The education level of individuals in a community is one of the indicators explaining the health of that community, and the performance of schools plays a significant role in promoting health and observing the educational justice of students and individuals in the community. Objectives: The present study aimed to compare the performance of support and public (rural) schools in Qom province concerning the preventive role of selected components in students' health. Methods: The present research is a descriptive comparative survey study. The statistical population included 17 Profit and Non-profit Rural schools in Qom province with 110 teachers and principals. First, the regions and schools were selected by cluster sampling method; then, through stratified sampling among profit and non-profit schools the proportion of gender and school type was observed, and through simple random sampling, 44 teachers and principals were chosen from among the selected schools. The research tool was a researcher-made questionnaire. To analyze the data, an independent t-test in SPSS version 16 software was used. Results: According to the findings of this study, the age range of participants was 22 to 51 years. Twenty-four participants (54.5%) had 1-10 years of teaching experience. Based on the data, the performance of profit schools was better than public (rural) schools in terms of the dimensions of planning, empowerment, health promotion, and physical education, and the performance of public (rural) schools was better than profit schools regarding the dimensions of education, learning, and executive and administrative affairs, which this difference was statistically significant (p≥0.001). There was no significant difference between the performance of profit schools versus public (rural) schools in the dimensions of developing participation in the school as well as the educational and complementary activities (p≥0.05). Conclusion: Given the differences in the dimensions of planning, education, learning, empowerment, health promotion, and physical education by this study, the officials' planning seems to play a preventive role in addressing the weaknesses in schools. However, performing more research in this regard is recommended